Pertumbuhan Ikan Tongkol Abu-Abu (Thunnus tonggol) yang Didaratkan di Pangkalan Pendaratan Ikan (PPI) Kedonganan - Mahmud, Muhammad Alfiansyah; Restu, I Wayan; Pratiwi, Made Ayu; Kartika, Gde Raka Angga (Current Trends in Aquatic Science; Vol 2 No 2 (2019), 2019)
Longtail Tuna fish (Thunnus tonggol) is one of economically important fish in the Bali Strait. The aim of this study was to assess the growth study of Longtail Tuna fish in the Bali Strait so as to provide an overview of the conditions and threats of Longtail Tuna fish landed at PPI Kedonganan. The study was conducted in November 2018 - January 2019. Data analysis consist of species composition, distribution of long frequencies, patterns and parameters of growth. Data processing was performed using Microsoft Excel and FISAT II. The results shown that Longtail Tuna fish landed at PPI Kedonganan included in fishermen's by-catchs and have a range of 418 mm - 643 mm. Longtail Tuna fish landed at PPI Kedonganan have growth pattern that is negative allometric (length increase is more dominant than weight gain) and parameters of growth  asymptotic length (Loo) is equal to 675.15 mm with growth coefficient (K) is 0.10/month in and a life span is 164 months.